DEVELOPMENT OF TECHNOLOGY FOR THE PREPARATION OF HEAVY-DUTY CONCRETE MIXTURES BY PROCESSING WITH AN ULTRASONIC MULTI-FREQUENCY ACOUSTIC FIELD - Dengaev, Alexey; Maksimenko, Alexandr; Shut, Konstantin; Novikova, Anna; Eremenko, Olga; Arteev, Kirill; Getalov, Andrey; Sargin, Boris; Safiullina , Elena (Journal of Applied Engineering Science, 2023)
The article presents the results of a study of the use of ultrasonic technologies to increase the strength of cement mortar in the production of building and concrete structures, as well as to improve the rheological parameters of grouting mortar during the construction (drilling) of wells. During the experiment, the concrete mortar was treated for 3 minutes with an ultrasonic multi-frequency acoustic field (frequency 20.0 - 40.0 kHz, signal power - 200-400 W/dm3) in devices of various geometric shape. Ordinary Portland Cement (OPC) of class G-100 was used in the composition of the solution without plasticizer additives in order to exclude their influence. The ratio of water and cement in the solution was 0.44, the density - 1.90 g/cm3. Typical elements of flow channels were used as volumes where ultrasonic exposure is carried out. The hydrodynamic regime of the processes in the water-cement suspension was modeled at the beginning of the experiments by slow mixing with a paddle agitator (200 rev./min), and on closing stage, in order to prevent the effect of hydrodynamic cavitation failure, at a speed of 1000 rev./min. The maximum compression and bending stresses are measured after the mixture solidified in a steam bath (T =60°C, 24 h.) on a hydraulic stand. Conducted experiments have confirmed that ultrasonic exposure using resonant accumulators and flow hoses: has a positive effect on the hydration reaction and the structure of cement stone in the concrete sealing phase; accelerates the intensity of compressive strength. (from 24.3 MPa to 41.5 MPa); uniformity of structure; reduces the influence of temperature on strength gain (reduces energy consumption); increases the reliability of building structures, and in the case of well construction - provides a strong adhesion of the production column with rock. In general, the results of the study allowed: to formulate a technology for the production of heavy-duty concrete mixtures; to develop a set of equipment for the preparation of concrete (grouting mortar) with specified characteristics at production objects.
Keywords: ultrasonic multi-frequency acoustic field, high-strength concrete mix, water separation of mortar, cement stone (paste), compressive and bending strength of concrete mix